Material Parameter Identification for a Stress-State-Dependent Ductile Damage and Failure Model Applied to Clinch Joining - Friedlein, Johannes; Böhnke, Max; Schlichter, Malte; Bobbert, Mathias; Meschut, Gerson; Mergheim, Julia; Steinmann, Paul (Journal of Manufacturing and Materials Processing)
Similar to bulk metal forming, clinch joining is characterised by large plastic deformations and a variety of different 3D stress states, including severe compression. However, inherent to plastic forming is the nucleation and growth of defects, whose detrimental effects on the material behaviour can be described by continuum damage models and eventually lead to material failure. As the damage evolution strongly depends on the stress state, a stress-state-dependent model is utilised to correctly track the accumulation. To formulate and parameterise this model, besides classical experiments, so-called modified punch tests are also integrated herein to enhance the calibration of the failure model by capturing a larger range of stress states and metal-forming-specific loading conditions. Moreover, when highly ductile materials are considered, such as the dual-phase steel HCT590X and the aluminium alloy EN AW-6014 T4 investigated here, strong necking and localisation might occur prior to fracture. This can alter the stress state and affect the actual strain at failure. This influence is captured by coupling plasticity and damage to incorporate the damage-induced softening effect. Its relative importance is shown by conducting inverse parameter identifications to determine damage and failure parameters for both mentioned ductile metals based on up to 12 different experiments.
Keywords: ductile damage; stress-state dependency; failure; parameter identification; punch test; clinching

Early childhood teachers' feedback in natural mathematical learning situations: Development and validation of a detailed category system - Aumann, Lena; Gasteiger, Hedwig; Puca, Rosa M. (Acta Psychologica)

Das Praxissemester aus Referendar:innenperspektive – Forschende Grundhaltung zwischen erster und zweiter Ausbildungsphase - Bloh, Thiemo; Homt, Martina; Bloh, Bea (Dokumentarische Professionalisierungsforschung bezogen auf das Lehramtsstudium)

Estimation of efficiency loss for stationary and moving structured packing columns using the hydrodynamic analogy approach - Ehlert, Thomas; Mamedov, Tural; Schubert, Markus; Kenig, Eugeny Y.

Aktuelle Befunde zur politischen Involviertheit von Lehramtsstudierenden in Nordrhein-Westfalen - Wehde, Janis; Bloh, Bea; Homt, Martina

Die Bedeutung von Praxisphasen für den eigenen Professionalisierungsprozess aus Referendar*innenperspektive - Bloh, Bea; Homt, Martina; Wehde, Janis

Perspektiven angehender Lehrkräfte auf Forschendes Lernen – eine qualitative Längsschnittstudie - Homt, Martina; Bloh, Bea; Wehde, Janis

Effekte eines partizipativen Lehrmoduls zur Demokratiebildung im Lehramtsstudium - Wehde, Janis (Zeitschrift für Hochschulentwicklung)
Der Beitrag untersucht die Effekte eines zwei Sitzungen umfassenden, partizipativen und themenunabhängig integrierbaren Lehrmoduls zur Stärkung der Demokratiebildungskompetenz von Lehramtsstudierenden (N = 159) in einer quasi-experimentellen Studie vom Sommersemester 2023 bis zum Sommersemester 2024. Die Ergebnisse der zweifaktoriellen Varianzanalysen mit Messwiederholungen (Pre-, Post- und Follow-up) verdeutlichen Effekte des Lehrmoduls auf die Selbstwirksamkeitserwartungen der Studierenden zur partizipativ-verfahrensorientierten Unterrichtsgestaltung und auf das methodische Wissen zur demokratischen Erarbeitung von Beurteilungskriterien in unterrichtlichen Lehr-Lern-Arrangements.

Überzeugungen von Lehramtsstudierenden zu Aspekten einer demokratischen Unterrichtsgestaltung - Wehde, Janis

Technologieakzeptanz beim Einsatz von Handhelds zur Unterstützung des Hörverstehens. Eine Datendiskussion - Hambach, Dennis

Philosophische Einmischungen. Abschiedsvorlesung, Universität Paderborn, 27.10.2023 - Peckhaus, Volker (Volker Peckhaus und Sebastian Luft: Philosophische Übergänge. Die Abschiedsvorlesung von Volker Peckhaus und die Antrittsvorlesung von Sebastian Luft im Oktober 2023)

Comparing transmission- and epi-BCARS: a round robin on solid-state materials - Hempel, Franz; Vernuccio, Federico; König, Lukas; Buschbeck, Robin; Rüsing, Michael; Cerullo, Giulio; Polli, Dario; Eng, Lukas M. (Applied Optics)
Broadband coherent anti-Stokes Raman scattering (BCARS) is a powerful spectroscopy method combining high signal intensity with spectral sensitivity, enabling rapid imaging of heterogeneous samples in biomedical research and, more recently, in crystalline materials. However, BCARS encounters spectral distortion due to a setup-dependent non-resonant background (NRB). This study assesses BCARS reproducibility through a round robin experiment using two distinct BCARS setups and crystalline materials with varying structural complexity, including diamond, 6H-SiC, KDP, and KTP. The analysis compares setup-specific NRB correction procedures, detected and NRB-removed spectra, and mode assignment. We determine the influence of BCARS setup parameters like pump wavelength, pulse width, and detection geometry and provide a practical guide for optimizing BCARS setups for solid-state applications.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Medienerziehung - Medienbildung - Herzig, Bardo; Tulodziecki, Gerhard (Handbuch Grundschulpädagogik und Grundschuldidaktik)

The individual and ecological characteristics of parental COVID-19 vaccination decisions - Hörnig, Lukas; Schaffner, Sandra; Schmitz, Hendrik (Scientific Reports)
Abstract Vaccination is a highly effective method to prevent the spread of COVID-19 and mitigate severe disease. In Germany, adult vaccination rates are relatively high at 85.5%, but rates are significantly lower for adolescents (69.6%) and children (20.0%). This discrepancy indicates that not all vaccinated parents choose to vaccinate their children. Analyzing data from a January 2022 online survey of 1,819 parents with children and adolescents, we explore the socio-economic factors influencing parents’ willingness to vaccinate themselves and their children. Our results show that individuals who vote for either side of the political extremes are less likely to vaccinate their children. This pattern is particularly strong for voters on the far right. In addition, we find that better educated parents are more likely to vaccinate both themselves and their children. Parents who vaccinate both themselves and their children demonstrate greater confidence in the vaccine’s effectiveness, while those who vaccinate only themselves are often motivated by a desire to regain personal freedoms. These insights highlight the need for targeted public health strategies to address specific concerns and improve vaccination rates among children and adolescents.

Rezension zu: Cazorla-Sánchez, Antonio; Ribeiro de Menezes, Alison; Shubert, Adrian (Hrsg.): The Bloomsbury Handbook of the Spanish Civil War London 2023 - Hansen, Christin (H-Soz-Kult)

Klimawandel und Gegenwartsliteratur - Schulte Eickholt, Swen (diMaG)
Zunehmend wird der Klimawandel prägender Faktor der Lebenswelten. Trotz innovativer technischer Lösungen scheint es schwer, zu einer Lebensweise zu finden, welche menschliches Leben mit dem Erhalt funktionierender Ökosysteme in Einklang bringt. Der Beitrag widmet sich der Frage, wie es dazu kommen konnte, dass Menschen die Welt so stark verändern, dass ihre eigene Zukunft bedroht ist und wie die Gegenwartsliteratur auf diese Frage reagiert hat. Zugespitzt zeigen sich in unterschiedlichen Kontexten, in denen dieser Frage nachgegangen werden kann, zwei Antworten: 1. Durch einen narrativen Trick ‒ zumeist eine leichte Verschiebung der Thematik ‒ wird ein Ende ermöglicht, das Hoffnung auf eine bessere Zukunft macht, 2. Der Mensch wird als Auslaufmodell gesehen, das entweder abgeschafft werden sollte oder durch unverbesserliches Weitermachen den Planeten nachhaltig zerstören wird.
Keywords: Klimawandel; Gegenwartsliteratur; Narrative; Anthropozän; Klimawandelroman

Religionspädagogik angesichts des jüdisch-christlichen Dialogs - Woppowa, Jan (Im Gespräch.Studienhandbuch zum jüdisch-christlichen Dialog)

Abschlussbericht: Auf dem Weg zu einer vergleichenden Erforschung kompositorischer Schaffensprozesse: Gemeinsame Terminologie und (digitale) philologische Modelle - Münzmay, Andreas; Novara, Elisa; Rovelli, Federica
Abschlussbericht Vom 13. bis 17. Mai 2024 fand in der Villa Vigoni ein internationales Kolloquium mit dem Titel Auf dem Weg zu einer vergleichenden Erforschung kompositorischer Schaffensprozesse: Gemeinsame Terminologie und (digitale) philologische Modelle statt: 21 Expert*innen aus verschiedenen musikhistorischen Fachgebieten (Komponisten; Regionen) wurden im Rahmen eines neuen Dialogformats zusammengebracht, um die Möglichkeiten einer gemeinsamen Terminologie für musikalische Schaffensprozesse zu erörtern. Die Diskussionen, die in italienischer und deutscher und englischer Sprache geführt wurden, bekräftigten die Notwendigkeit, den eingeschlagenen Weg fortzusetzen und legten den Grundstein sowohl für den Aufbau eines internationalen Netzwerks von Wissenschaftlern als auch für eine synergetische Zusammenarbeit zwischen verschiedenen Forschungsinstituten

Software Security Analysis in 2030 and Beyond: A Research Roadmap - Böhme, Marcel; Bodden, Eric; Bultan, Tevfik; Cadar, Cristian; Liu, Yang; Scanniello, Giuseppe (ACM Transactions on Software Engineering and Methodology)
As our lives, our businesses, and indeed our world economy become increasingly reliant on the secure operation of many interconnected software systems, the software engineering research community is faced with unprecedented research challenges, but also with exciting new opportunities. In this roadmap paper, we outline our vision of Software Security Analysis for the systems of the future. Given the recent advances in generative AI, we need new methods to assess and maximize the security of code co-written by machines. As our systems become increasingly heterogeneous, we need practical approaches that work even if some functions are automatically generated, e.g., by deep neural networks. As software systems depend evermore on the software supply chain, we need tools that scale to an entire ecosystem. What kind of vulnerabilities exist in future systems and how do we detect them? When all the shallow bugs are found, how do we discover vulnerabilities hidden deeply in the system? Assuming we cannot find all security flaws, how can we nevertheless protect our system? To answer these questions, we start our roadmap with a survey of recent advances in software security, then discuss open challenges and opportunities, and conclude with a long-term perspective for the field.

The neural network approach for estimation of heat transfer coefficient in heat exchangers considering the fouling formation dynamic - Ilyunin, Oleg; Bezsonov, Oleksandr; Rudenko, Sergiy; Serdiuk, Nataliia; Udovenko, Serhii; Kapustenko, Petro; Plankovskyy, Sergiy; Arsenyeva, Olga (Thermal Science and Engineering Progress)